2010
DOI: 10.1002/ange.200904948
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoramidite: privilegierte Liganden in der asymmetrischen Katalyse

Abstract: Die asymmetrische Katalyse mit Übergangsmetallkomplexen ist die Grundlage unzähliger stereoselektiver Umwandlungen und hat damit das Bild der modernen Synthesechemie gewandelt. Der Schlüssel zum Erfolg war die Entwicklung chiraler Liganden zur Kontrolle der Regio‐, Diastereo‐ und Enantioselektivität. Dabei haben sich Phosphoramidite als eine äußerst vielseitige und leicht zugängliche Klasse von chiralen Liganden erwiesen. Ihre modulare Struktur ermöglicht die Herstellung von Ligandenbibliotheken und erleichter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(61 citation statements)
references
References 507 publications
1
54
1
5
Order By: Relevance
“…It has been reported that certain additives, such as tetrahydrothiophene, and triphenylphosphine with copper(I) iodide or Pb(II) acetate, can enhance both stereoselectivity and conversion in such iridium catalyzed Tsuji-Trost allylations. [19] However, in our hands, these additives completely suppressed the reaction.…”
Section: Resultscontrasting
confidence: 49%
“…It has been reported that certain additives, such as tetrahydrothiophene, and triphenylphosphine with copper(I) iodide or Pb(II) acetate, can enhance both stereoselectivity and conversion in such iridium catalyzed Tsuji-Trost allylations. [19] However, in our hands, these additives completely suppressed the reaction.…”
Section: Resultscontrasting
confidence: 49%
“…[1,2] Since the first asymmetric reaction enabled by an Ir/Phox complex, introduced by the group of Helmchen, [3] the development of chiral ligands has been one of the most important tasks in this field. Among the many chiral ligands used, the bulk of work on iridium-catalyzed allylic substitution reactions mainly focused on catalysts derived from chiral phosphoramidite ligands, represented by the Feringa [4] /Alexakis [5] P,C ligands and Carreira P,olefin ligand [6] (Figure 1). In particular, the Feringa and Alexakis ligands have been proven to be privileged ones, thus affording excellent regio-and enantioselectivity.…”
mentioning
confidence: 99%
“…Encouraged by this result, we directed our attention to the development of the Pd-catalysed asymmetric[ 3 + +2] cycloaddition reactionw ith 1b and 2a as model substrates. Firstly,aseries of BINOL-derived chiral phosphite amide ligands [12] weree valuated for this reaction. For example, the reactionu sing the dimethyl-substituted chiral ligand L1 produced the chiral product 3b in modest yield as well as diastereo-and enantioselectivity (entry 3).…”
Section: -13-dipoles:adivergent Approach To Enantioenriched Spirooximentioning
confidence: 99%